The spoU gene of Escherichia coli, the fourth gene of the spoT operon, is essential for tRNA (Gm18) 2'-O-methyltransferase activity. - Persson, B C (1997)
We have evidence that the open reading frame previously denoted spoU is necessary for tRNA (Gm18) 2'-O-methyltransferase activity. The spoU gene is located in the gmk-rpoZ-spoT-spoU-recG operon at 82 minutes on the Escherichia coli chromosome. The deduced amino acid sequence of spoU shows strong similarities to previously characterized 2'-O-methyltransferases. Comparison of the nucleoside modification pattern of hydrolyzed tRNA, 16S rRNA and 23S rRNA from wild-type and spoU null mutants showed that the modified nucleoside 2'-O-methylguanosine (Gm), present in a subset of E. coli tRNAs at residue 18, is completely absent in the spoU mutant, suggesting that spoU encodes tRNA (Gm18) 2'-O-methyltransferase. Nucleoside modification of 16S and 23S rRNA was unaffected in the spoU mutant. Insertions in the downstream recG gene did not affect RNA modification. Absence of Gm18 in tRNA does not influence growth rate under the tested conditions and does not interfere with activity of the SupF amber suppressor, a suppressor tRNA that normally has the Gm18 modification. We suggest that the spoU gene be renamed trmH (tRNA methylation).